Mevalonate pathway-triggered phase transition of injectable hydrogel for cholesterol-downregulated therapy of osteoarthritis - Akhmad Irhas Robby; Ee Hyun Kim; Kang Moo Huh; Eun-Jung Jin; Ki Dong Park; Sung Young Park (Bioactive Materials, 2025)
Dysregulation of mevalonate pathway, an essential metabolic route involving coenzyme A (CoASH) and cholesterol, contributes significantly to escalating cartilage degradation. Existing treatments rely on the simvastatin delivery via tunable sol-gel transition mechanisms of injectable hydrogel. However, those methods suffer from lack of controllable drug release by selective phase transition under distinct disease microenvironment. Herein, we developed an aberrant lipid metabolism microenvironment-activated phase transition (normal condition: gel-gel, abnormal condition: gel-sol) with targeted drug release for synergistic treatment of osteoarthritis (OA). Naked-eye diagnosis and therapy of OA through cholesterol downregulation using an injectable hydrogel were based on the simvastatin-loaded nanoparticles embedded in hexanoyl glycol chitosan (HGC-SIM@PAA-MnO2-cPDA or SIM gel). The interaction between highly expressed CoASH in OA and PAA-MnO2 in SIM gel altered the hydrophobic–hydrophilic balance and gelation temperature, triggering the OA-sensitive gel-sol transformation. Naked-eye gel-sol transformation was observed after incubating SIM gel with OA chondrocyte models, including acetyl-CoA-induced wild-type (WT + CoA), NudT7−/− knockout (N7KO), and Acot12−/− knockout (A12KO). Because of the simvastatin release after gel-sol transition, OA-related enzymes and genes, including antioxidant enzymes (Sod2), cartilage degradation genes (Adamts4), and cholesterol synthesis-related enzymes (Mvk), were downregulated. In vivo studies revealed gel-sol transformation in destabilized medial meniscus of OA mice (DMM WT, N7KO, and A12KO) at 4–8 weeks post-injection, with significantly reduced cartilage degradation, demonstrating theragnostic capability of SIM gel. Thus, SIM gel offers a potential approach for future synergistic OA diagnosis and therapy.